Efeito do Sexo e do Peso ao Abate sobre a Produção de Carne de Cordeiro. Morfometria da Carcaça, Pesos dos Cortes, Composição Tecidual e Componentes Não Constituintes da Carcaça - De Siqueira, Edson Ramos [UNESP]; Simões, Christian Deodato; Fernandes, Simone [UNESP] (My University, 2001)
This experiment was carried out to evaluate the effects of sex (males x females) and four slaughter weights (28, 32, 36 and 40 kg), on carcass morphometry, cuts weights, tissues and offals percentages, from crossbred lambs Ile de France x Corriedale, finished in feedlot. Fourty lambs (20 males and 20 females), were weaned at 60 days of age and were full fed a diet with 16.46% CP and 67.63% TDN. They were divided in 4 male groups (G1M, G2M, G3M and G4M), slaughtered respectively with the mentioned weights, and, in the same way, 4 female groups (G1F, G2F, G3F and G4F). It was determined the carcass measures, body score, carcass conformation and fat grades; carcass and leg compacity index; the weights and porcentages of 7 cuts from the half carcass; muscle, bone and fat tissue percentages from the loin and fat thickness on the loin. The morfometric study showed a higher osseous elongation in the males carcasses. Generally, the compacity index indicated a good carcass finishing. The female carcass cuts were heavier than the male cuts (except for the live weight of 28 kg), ascribed to the higher fat content. Among the offals, skin and gastrointestinal content weights showed to be highly representative in the carcass yield determination. Finally, it is recommended the slaughter weight of 28 kg.
Sex and Slaughter Weight Effects on Meat Production of Lambs. Carcass Morphometric Evaluation, Cuts Weights, Tissues and Offals Percentages
Keywords: Lamb carcass; Lamb meat; Lamb offals; Lamb production; Sheep